Real-World Treatment Patterns and Clinical Outcomes in Patients With Stage III Non-Small-Cell Lung Cancer: Results of KINDLE-Vietnam Cohort - Van Dao, Tu; Diep, Tuan Bao; Le Phuong, Tri; Huggenberger, Reto; Kumar, Amit (Frontiers in Oncology, 2022)
Objective KINDLE-Vietnam was a part of a real-world KINDLE study with an aim to characterise treatment patterns and clinical outcomes of patients with stage III non-small cell lung cancer (NSCLC). Materials and Methods Retrospective data from patients diagnosed with stage III NSCLC (American Joint Committee on Cancer, 7th edition) between January 2013 and December 2017 with at least 9 months of follow-up were collected from two centres in Vietnam. Descriptive statistics were used to summarise demographics, disease characteristics and treatment modalities. Kaplan-Meier methodology evaluated survival estimates; two-sided 95% confidence intervals (CIs) were computed. Inferential statistics were used to correlate clinical and treatment variables with median progression-free survival (mPFS) and median overall survival (mOS). Results A total of 150 patients (median age: 60 years [range 26-82]) were enrolled; 75.3% were male; 62.0% had smoking history; 56.4% had stage IIIB disease; and 62.5% had adenocarcinoma. The majority of the cases (97.3%) were not discussed at a multi-disciplinary team meeting. Overall, chemotherapy alone (43.3%), radiotherapy alone (17.0%), sequential chemoradiation (13.5%) and concurrent chemoradiation (12.8%) were preferred as initial therapy. Surgery based treatment was administered in limited patients (stage IIIA; 10% stage IIIB, 1.3%). Palliative therapy was the most commonly administered treatment upon relapse in the second-and third-line setting. The mPFS and mOS for the Vietnam cohort were 8.7 months (95% CI, 7.59-9.72) and 25.7 months (95% CI, 19.98-42.61), respectively. The mPFS and mOS for stage IIIA were 11.9 months (95% CI, 8.64-14.95) and 28.2 months (95% CI, 24.15-not-calculable) and stage IIIB were 7.8 months (95% CI, 6.64-8.71) and 20.0 months (95% CI, 13.01-42.61). Conclusions KINDLE-Vietnam offers insights into the clinical findings of stage III NSCLC. There is a high unmet need for identifying patients in the early stages of NSCLC. Strategies for improving clinical outcomes in this patient population include physician education, multi-disciplinary management and catering to increased access to novel agents like immunotherapy and targeted therapy.